Contrast-enhanced ultrasonography for differential diagnosis of adnexal masses - Shentu, Weihui; Zhang, Yin; Gu, Jiaojiao; Wang, Fa; Zhao, Wei; Liu, Chunmei; Lin, Zimei; Wang, Yao; Liu, Chen; Chen, Yunyu; Fan, Qiyun; Wang, Hongying (Frontiers in Oncology, 2022)
Background Quantitative contrast-enhanced ultrasonography parameters are affected by various factors. We evaluated corrected quantitative contrast enhanced ultrasonography in differentiating benign adnexal tumors from malignant tumors. Methods Patients with adnexal masses who underwent conventional and contrast-enhanced ultrasonography were included. Contrast-enhanced ultrasonography parameters such as base intensity, arrival time, peak intensity, time to peak intensity, ascending slope, and descending slope were measured. Corrected (time to peak intensity − arrival time) mass/(time to peak intensity − arrival time) uterus and (peak intensity − base intensity) mass/(peak intensity − base intensity) uterus were calculated. Lesions were confirmed by pathologic examination of surgical specimens. Results This study included 31 patients with 35 adnexal lesions including 20 (57.10%) benign and 15 (42.90%) malignant lesions. The corrected contrast-enhanced ultrasonography quantitative parameters in lesions were statistically different between malignant and benign groups (P<0.05). The optimal cut-off value for (time to peak intensity − arrival time) mass/(time to peak intensity − arrival time) uterus, ascending slope, and (peak intensity − base intensity) mass/(peak intensity − base intensity) uterus, and descending slope for differentiating malignant adnexal masses from benign tumors were 1.05 (area under curve: 0.93, P<0.05), 1.11 (area under curve: 0.83, P<0.05), 0.82 (area under curve: 0.73, P<0.05), and −0.27 (area under curve: 0.66, P=0.16), with sensitivity and specificity of 93.33% and 85.00%, 86.67% and 75.00%, 86.67% and 60.00%, and 54.55% and 66.67%, respectively. Conclusions Corrected contrast-enhanced ultrasonography parameters provide practical differential diagnosis value of adnexal lesions with high reliability for sonologists.